2018
DOI: 10.1007/s00520-018-4304-0
|View full text |Cite
|
Sign up to set email alerts
|

The impact of automated screening with Edmonton Symptom Assessment System (ESAS) on health-related quality of life, supportive care needs, and patient satisfaction with care in 268 ambulatory cancer patients

Abstract: Significant correlation between change in ESAS and HRQoL implies ESAS could usefully inform healthcare providers about need to respond to changes in symptom and functioning between visits. This study showed no impact of early-ESAS screening on HRQoL or PSC. Further research should explore how to better utilize ESAS screening, to improve communication, symptom management, and HRQoL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 41 publications
0
28
0
Order By: Relevance
“…Previous research investigating the association between needs assessment and improved outcomes has predominantly focused on measuring impact through a range of measurable outcomes such as distress, anxiety, depression and pain using specific tools such as the Distress Thermometer (DT) [26][27][28]. Qualitative evidence on the use of HNA has shown that it can improve communication between patients and clinicians, providing an opportunity to discuss non-clinical concerns and signpost patients to a variety of different services [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research investigating the association between needs assessment and improved outcomes has predominantly focused on measuring impact through a range of measurable outcomes such as distress, anxiety, depression and pain using specific tools such as the Distress Thermometer (DT) [26][27][28]. Qualitative evidence on the use of HNA has shown that it can improve communication between patients and clinicians, providing an opportunity to discuss non-clinical concerns and signpost patients to a variety of different services [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research investigating the association between needs assessment and improved outcomes has predominantly focused on measuring impact through a range of measurable outcomes such as distress, anxiety, depression and pain using speci c tools such as the Distress Thermometer (DT) [26][27][28]. Qualitative evidence on the use of HNA has shown that it can improve communication between patients and clinicians, providing an opportunity to discuss non-clinical concerns and signpost patients to a variety of different services [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research investigating the association between needs assessment and improved outcomes has predominantly focused on measuring impact through a range of measurable outcomes such as distress, anxiety, depression and pain using specific tools such as the Distress Thermometer (DT) (21)(22)(23). Qualitative evidence on the use of HNA has shown that it can improve communication between patients and clinicians, providing an opportunity to discuss non-clinical concerns and signpost patients to a variety of different services (24,25).…”
Section: Discussionmentioning
confidence: 99%